Concentración de metales en el suelo y su relación con el contenido en Manihot esculenta (yuca) cultivada de la zona de Puerto Almendra Nina Rumi, Loreto - Calloapaza Valladares, Carlos Enrique (2022)
The research was aimed at relating the concentration of metals in the soil with the content of Manihot esculenta (yucca) crops in the areas of Puerto Almendra Nina Rumi, Loreto. The study was of a correlational type at a cross-sectional descriptive level, with an experimental design during the months of May to July 2021, the technique was observation and the instrument the protocol for the concentration of the analyte by atomic absorption, in the cultivation soil, in root and leaves of the Manihot esculenta plant (yucca) and the content in mg / kg (ppm) of metals was considered: Fe, Cu, Cr, Mn, Zn, Cd and Pb. The study determined that the concentration of metals in the soil at the depths of 0-20 cm and 20-40 cm, were above the normal parameters established by the ECA, with respect to the first depth, the highest was Manganese between 195-201 ppm and the lowest was Cadmium between 0,07-0,08 ppm, also for the second depth Manganese also presented the highest parameter between 210-213 ppm and the lowest was Cadmium between 0,08 – 0,09 ppm. Likewise, the concentration of metals in the leaves and the root of the Manihot esculenta (yucca) cultivated in the area of Puerto Almendra Nina Rumi, were above the allowed values, in the leaves the Manganese presented values between 185-187,75 ppm and Cadmium ranged between 0,02-0,03 ppm; being the only metal that was slightly within its normal range ? 0,02 ppm), in the root Iron varied between 83-83,85 ppm and Cadmium between 0,025-0,03 ppm; being the only metal that slightly exceeded the normal range of ? 0,02 ppm; the concentrations being higher in the leaf than in the root. What indicates the higher the concentration of metals in the soil, the greater the concentration in the leaves and the root of Manihot esculenta (Yucca). To this end, it seeks to propose alternatives to avoid metal poisoning in food for human consumption through the proposal of a program for the presumptive detection of metals contained in cassava in the Puerto Almendra area.